OPTIMIZATION OF MOUNTAIN BIKE FRAME DESIGN: LOADING VARIATIONS USING HIGH STRENGTH CARBON - Ivan Wiyarta Cakra Sujana, I Made; Batubara, Yongki Christandi; Rahmany, Rijal Surya (ROTOR, 2024)
Mountain bikes have become a popular mode of transportation and recreation among extreme sports enthusiasts. A strong and lightweight frame design is crucial to support performance and ensure rider safety, especially in challenging terrain conditions. This study aims to explore the optimization of mountain bike frame design with a focus on the use of high-strength carbon materials. The research evaluates the performance and durability of the frame through Von Mises stress analysis, displacement, and safety factor under load variations of 65 kg, 70 kg, and 75 kg. The analysis results show that the stress increases with the load, from 7.298 MPa at 65 kg to 8.421 MPa at 75 kg. Displacement also increases, from 0.004982 mm to 0.005748 mm. The safety factor remains above 15, indicating a high safety margin for the material. These findings suggest that although stress and deformation increase, the frame design still meets the strength standards required for user safety. This research contributes significantly to the development of more efficient, sustainable bicycles, and serves as a reference for manufacturers in designing safe and comfortable products. Recommendations for further testing include dynamic load analysis to understand the frame's behavior under real-world usage conditions. Keywords: AL 6061, Mountain Bike Frame, Simulation